The Suitability of Legal Rules Related to Intellectual Property to Protect Digital Works Derived by Artificial Intelligence - Al Hammadi, Zainab; Abd al-Hay, Imad al-Din (Journal of Legal Sciences, 2026)
Devoting a study to the suitability of the legal rules in force to protect digital works derived by artificial intelligence is of great importance in the areas of intellectual property. This sparked a jurisprudential debate about considering digital works derived with artificial intelligence as an invention, just like traditional works, as well as disagreement over the ownership of digital works derived with artificial intelligence, and the lack of legal rules to regulate these matters. Therefore, the question has arisen about the suitability of the current legal rules to accommodate and organize digital works devised by artificial intelligence, and in our topic, devising intelligent digital works. For this reason, the idea of ​​this important research came about, which comes in the context of legal regulation of digital works derived by artificial intelligence? The researcher raises the question: Do current literary and artistic property legislation accommodate artificial intelligence inventions, such as smart digital works, and consider artificial intelligence as an inventor? If the answer is no; We wonder whether this legislative position should be reconsidered in light of the major technological developments underlying the field of artificial intelligence. Is it time to consider artificial intelligence systems as inventors under the legal regulation of literary and artistic property, specifically copyright protection? The research reached several results, the most important of which is that technological development in the field of artificial intelligence has produced digital works independently devised by artificial intelligence, and inventions devised with the help of artificial intelligence, and these smart digital works are not regulated in copyright legislation. Based on the fact that legal legislation is only known to human inventors (the natural person), and does not recognize artificial intelligence as an inventor, and does not grant it legal protection. Because it does not have legal personality, and current legal legislation is not appropriate to accommodate artificial intelligence inventions. The research also reached several recommendations, the most important of which is establishing an independent legal regulation for digital works derived with artificial intelligence. Because any adaptation of traditional rules will result in legislative distortion of literary and artistic ownership texts. That is, amending literary and artistic property legislation, specifically copyright; To accommodate digital classifiers derived by artificial intelligence.